2014
DOI: 10.1097/cmr.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of abnormally expressed long noncoding RNA UCA1 and Malat-1 in metastasis of melanoma

Abstract: Melanoma is a highly aggressive skin cancer with increasing incidence worldwide. Long noncoding RNAs (lncRNAs), a group of nonprotein-coding transcripts longer than 200 nucleotides, are pervasively transcribed in the genome and are emerging as new players in tumorigenesis. The primary objective of this study was to investigate the role of six cancer-related lncRNAs in pairs of melanoma and adjacent normal tissues (ANTs). A total of 63 primary melanoma, paired ANTs, and metastatic lesions were collected in a Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 25 publications
1
109
2
Order By: Relevance
“…80 Knockdown of HOTAIR inhibited the motility and invasiveness of melanoma cells, with decreased degradation of extracellular matrix. 80 Another study by Tian et al 81 found no statistical difference in expression levels of HOTAIR lncRNA between melanoma and adjacent normal tissue. This observation was attributed to the inclusion criteria of the study that restricted samples only to superficial spreading and nodular melanomas.…”
Section: Hox Transcript Antisense Rna (Hotair)mentioning
confidence: 99%
See 4 more Smart Citations
“…80 Knockdown of HOTAIR inhibited the motility and invasiveness of melanoma cells, with decreased degradation of extracellular matrix. 80 Another study by Tian et al 81 found no statistical difference in expression levels of HOTAIR lncRNA between melanoma and adjacent normal tissue. This observation was attributed to the inclusion criteria of the study that restricted samples only to superficial spreading and nodular melanomas.…”
Section: Hox Transcript Antisense Rna (Hotair)mentioning
confidence: 99%
“…102 MALAT1 is highly expressed in melanoma compared to adjacent normal tissues. 81 Knockdown studies showing an effect of MALAT1 on migration of melanoma cells suggest that MALAT1 may promote melanoma spread as with UCA1. 81 …”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%
See 3 more Smart Citations